Status of Female Adolescents Living at Rajshahi Slum in Bangladesh - Choudhary, Md. Shahidur Rahman; Rahman, Md Mahfuzar (Bangladesh Journal of Medical Science, 2015)
Objective: To avoid the social consequences of unplanned pregnancy, transmission of STIs and HIV/AIDS, adolescents need to be awaked of their reproductive health. That is why; the study is aimed to know the present status of adolescents in terms of socio-demographic and menstrual management status living in slum areas of Rajshahi City Corporation (RCC), Bangladesh. Materials and methods: The data for this study were collected purposively in 2012 from 200 girls aged 10-19 who were slum living at RCC using a pre-designed questionnaire. The purpose and importance of this study were explained to the respondents before participating in this study. Results and discussion: The result showed that 64% of the respondents were in the group of 18-19 years. Around 9.5% of the adolescents had never gone to school. The maintenance of hygiene during menstruation is a vital aspect of adolescent reproductive health. But the result showed that about 94% of the respondents answered that they do not know the underlying reasons for what menstruation occurred. Only 5% of the respondents maintained some form of hygiene measurements (pad or clean cloth) during the onset of their menstruation. The result also indicated that 24.5% of the respondents felt physical illnesses during their menstruation. Conclusion: The authority should commit to ensuring that the needs, challenges, aspirations, vulnerabilities and rights of adolescents, especially for girls, are fully considered in this new development agenda. Keeping this in mind, adolescent friendly health services should be ensured by arranging special hours or special days for them, orienting and providing training to healthcare providers on how to counsel adolescents. DOI: http://dx.doi.org/10.3329/bjms.v14i1. Bangladesh Journal of Medical Science Vol.14(1) 2015 p.